Involuntary psychiatric treatment during the COVID-19 pandemic. An international qualitative study - Carbone, Agostino; Knapp, Martin (Frontiers in Psychiatry, 2023)
Background During the COVID-19 pandemic, studies report that in the first few months of the lockdown there was a decrease in requests for mandatory psychiatric treatment, while, in contrast, following the second wave, the number of cases increased. This study investigates the use of compulsory psychiatric treatments internationally in the first and subsequent phases of the pandemic. Methods Sixteen key people were interviewed: eight mental health care professionals and eight scholars in Italy, Greece, China and Chile. Participants were asked to discuss their experience of the motivations, diagnoses and management of patients undergoing an involuntary psychiatric hospitalization. Results The analysis through Grounded Theory highlighted four themes: (a) the culture of psychiatric care services, (b) the effect of the pandemic on involuntary hospitalizations, (c) exceptional management of hospitalization, and (d) policies and suggestions for more inclusive mental health treatments. Conclusion During the first wave, respondents reported a decrease in the use of involuntary treatments, while a gradual increase was seen in the following months. Italy extended compulsory psychiatric treatment to a group of new users, including young people and adolescents with acute crises; in other contexts, the main users are chronic psychiatric patients.